Subtracted Adulthood Mass Index - a new index to predict NAFLD risk in non-obese individuals - Kiyak, Ata; Elibol, Serra; Barutcu, Ozlem; Saruc, Murat; Tozun, Nurdan (KARE PUBL, 2021)
Background and Aim: Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease. The aims of the current study are to determine the relationship between NAFLD in non-obese individuals and weight gain during adulthood and develop a new index for the identification of NAFLD risk. Materials and Methods: For this cross-sectional study, 362 patients who underwent abdominal ultrasonography (USG) in our clinic were included. Seventy-eight individuals were obese (>30 kg/m(2)). A history of weight gain during adulthood and systemic metabolic diseases was collected at the time of the study. A new index termed ``Subtracted Adulthood Mass Index{''} (SAMI) was created to estimate the risk of NAFLD development for non-obese people. SAMI is the ratio of the difference between the individual's current weight and his/her weight at 20 years old to his/her height squared (kg/m(2)). Results: When the SAMI cut-off was set at 3 kg/m(2), the sensitivity for predicting NAFLD risk was 85.2\%, the specificity was 66.9\%, the PPV was 79.1\%, and the NPV was 75.4\%. Conclusion: In this innovational study, a new index named SAMI was developed to identify non-obese people who are at risk of developing NAFLD. The SAMI is easy to calculate and appropriate for clinical use.
Keywords: NAFLD; nonalcoholic fatty liver disease; weight gain in adult-hood